Antibacterial effect of the nanoparticle-incorporated primers commonly used for orthodontic bonding - Ekta Gupta; Tejas A Chaugule; Ajay K Kubavat; Preetham Ravuri; Katha Mandal; Praveen K Varma (Wolters Kluwer Medknow Publications, 2024)
Background: Nanosized antibacterial agents can be used to prevent biofilm buildup on orthodontic appliances and auxiliaries, limiting microbial adherence and preventing caries. Nanoparticles (NPs) can enhance the antibacterial properties of orthodontic materials due to their smaller particle size and larger surface area. Materials and Methods: The study's material analysis was divided into four groups, numbered I through IV, using Transbond XT Primer as a control and modifying group I by adding various antibacterial agents. 98.1 g of mutans-sanguis agar was dissolved in 1,000 ml of warm distilled water and autoclaved for 15 minutes at 121°C and 15 lb pressure. 176 disk specimens of 6 mm in diameter were created, sterilized in an autoclave, and heated to 60°C in a hot air oven for 1 hour. Ten milliliters of primer containing different antimicrobial agents was applied to the sterilized disks. Four petri plates were used for each concentration, with 16 disks in each group. 44 petri plates in all were utilized. Results: The orthodontic primer modified by the addition of antibacterial agents showed a significantly increased antimicrobial activity, and nanobenzalkonium chloride (BAC) at 5% concentration showed the highest antimicrobial efficacy among all groups. Nanohydroxyapatite showed the least. Conclusion: Within the confines of the current investigation, it was determined that the addition of antibacterial agents had significantly higher antimicrobial activity and BAC at 5% concentration had the highest antimicrobial efficacy of all the groups.